Study of cyclophosphamide removal by using sodium hypochlorite: A case study on hospitals sewage - Elham Asrari; Afsane Saemian (Journal of Applied Research in Water and Wastewater)
Due to the increasing incidence of cancer, the consumption of anti-cancer or neoplastic drugs has increased significantly. These compounds are not removed during wastewater treatment with sufficient efficiency, they could be found in the groundwater. Oxidation is an efficient method for removing neoplastic drugs such as cyclophosphamide. The previous researchers could make use of a wide range of oxidants because of compiling the health protocols for the lowest risk of drug hazards. The purpose of this research is to remove cyclophosphamide residue in vomit contents, urine, or feces of patients through toilet sewage that merges with household sewage or municipal sewage. In this study, all experiments were done by the oxidation method of cyclophosphamide 10 mg/L with sodium hypochlorite and considering of effectiveness of pH changes and reaction time. It was shown that cyclophosphamide degradation has increased with increased concentration of sodium hypochlorite and reaction time at pH=9.8. The destructive 94.8% of cyclophosphamide was optimized by the concentration of 0.02 % sodium hypochlorite, pH=9.8, and a reaction time of 5 min. Also, the comparative results of drug removal in hospital wastewater with optimal concentration, pH, and time showed increasing of 4% reduction in cyclophosphamide drug removal (98.02%) compared to the test sample. The result of the research can be effective in removing cyclophosphamide by installing a dosing pump in the flush tank or toilet siphon of the oncology department.